ANALISIS KOMODITAS UNGGULAN DAN ARAHAN RENCANA PENGEMBANGANNYA DI KOTA PAGAR ALAM,PROVINSI SUMATERA SELATAN - Ahmad Zamhari; Santun R.P. Sitorus; Andrea Emma Pravitasari (Diponegoro University, 2017)
The Development of competitive commodities in a region are expected to improve added value of the commodities, to increase society income and to improve regional economic conditions. This study was conducted (1) to analyse competitive commodities of agriculture in each district, (2) to analyse potential land for competitive commodities development (3) to analyse regional hierarchies (4) to formulate direction of competitive commodities development plan. The competitive commodities were obtained using Location Quotient (LQ) and Shift Share Analysis (SSA). Analysis potential land for competitive commodities development was analysed using land availability and suitability and geographical information system. Regional hierarchy was analysed using schalogram method. Competitive commodities development direction considered based on potential land, regional hierarcy, compactness of land and local government policy. The results showed that competitive commodities in every district were coffee robusta, rice farming and cabbage. The direction development of coffee was given priority in South Dempo district area of 2,824.26 ha. Rice farming was given priority in Central Dempo district area of 1,496.13 ha. Meanwhile, development of cabbage is not available.